Kajian Emisi Karbon Dioksida pada Berbagai Tipe Penggunaan Lahan Gambut di Kalimantan - , Nyahu Rumbang, Ir.,MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Study of carbon dioxide emissions in different types of peatlands use in Central and West Kalimantan has been conducted in January-June 2006 and January-April 2007. The study represents 4 types of land use in Central Kalimantan as treatment: 5 years for chinesse cabbage, 10 years for chinesse cabbage, 5 years for sweet corns, and 10 years for sweet corns. As for the treatments in West Kalimantan, they include corn field, Aloe vera field, oil palm plantation, and rubber plantation. Carbon dioxide was measured using infrared gas analysis (model EGM-4, PP systems, Hitchin, UK). In Central Kalimantan, the highest CO2 is emitted from sweet corn plants (arable land for 10 years) by 0.79 g CO2/m2/hour, chinesse cabbage plants (for 5 years) by 0.73 g CO2/m2/hour, chinesse cabbage plants (for 10 years) by 0.67 g CO2/m2/hour and, the least, sweet corn plants (for 5 years) by 0.41 g CO2/m2/hour. The highest CO2 emission from West Kalimantan is released from rubber plants at 1.22 g CO2/m2/hour, followed by palm oil plants by 0.96 g CO2/m2/hour, Aloe vera plants by 0.68 g CO2/m2/hour and corn plants by 0.35 g CO2/m2/hour. Groundwater table depth are the most important factors among other factors that influence CO2 emissions. Groundwater table depth indicated a positive correlation with CO2 emissions in all types of peatlands use. C-organic production of sweet corn plants at 11.66 t C/ha/year is higher than that of chinesse cabbage plants at 1.64 t C/ha /year. Corn plants produce organic-C was 11.66 t C/ha/year, equivalent to the amount of loss of C through CO2 emissions by 11.29 t C/ha/year.